2012
DOI: 10.1016/j.bbmt.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Infusional Gemcitabine Combined with Busulfan and Melphalan with Autologous Stem-Cell Transplantation in Patients with Refractory Lymphoid Malignancies

Abstract: We developed a new high-dose combination of infusional gemcitabine with busulfan/melphalan for lymphoid tumors. Gemcitabine dose was escalated by extending infusions at a fixed rate of 10 mg/m2/min in sequential cohorts, in daily, 3-dose or 2-dose schedules. Each dose immediately preceded busulfan (adjusted targeting AUC 4,000 μM.min−1/day × 4 days) or melphalan (60 mg/m2/day × 2 days). We enrolled 133 patients (80 Hodgkin’s lymphoma (HL), 46 non-Hodgkin’s lymphoma (NHL), 7 myeloma), median 3 prior regimens; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 51 publications
9
74
1
1
Order By: Relevance
“…Furthermore, little is known regarding the comparative toxicity and efficacy of various regimens applied in lymphomas. Thus, no safe conclusions can be made due to the lack of randomized trials, and conditioning regimens for AHCT in lymphomas melphalan or busulfan, etoposide and cyclophosphamide) [45] resulting in a lower outcome than achieved post-BuEM, and TRM at 100 days of 5.5% versus zero in the BuEM group [46]. It is noteworthy that our findings suggest that administration of BuEM contributes to superior OS in patients with HL despite their prevalent poor risk features.…”
Section: Non-hematological Toxicitycontrasting
confidence: 49%
“…Furthermore, little is known regarding the comparative toxicity and efficacy of various regimens applied in lymphomas. Thus, no safe conclusions can be made due to the lack of randomized trials, and conditioning regimens for AHCT in lymphomas melphalan or busulfan, etoposide and cyclophosphamide) [45] resulting in a lower outcome than achieved post-BuEM, and TRM at 100 days of 5.5% versus zero in the BuEM group [46]. It is noteworthy that our findings suggest that administration of BuEM contributes to superior OS in patients with HL despite their prevalent poor risk features.…”
Section: Non-hematological Toxicitycontrasting
confidence: 49%
“…However, Bu was used under the control of daily monitoring and adaptation in accordance with area under the curve analysis. Nieto et al 77 reported another study comparing GemBuM with BEAM and BuM (Bu administered as a single dose). Toxicity seemed equivalent between regimens; however, there were better survival results with GemBuM.…”
Section: Conditioning Regimens For Lymphoma G Damaj Et Almentioning
confidence: 99%
“…SOS was not reported. Nieto et al 77 used a single dose of Bu in combination with Gem and melphalan in 133 HL, 47 NHL and 7 myeloma cases. Toxicity appeared equivalent to other conditioning treatments, except for cutaneous toxicity, which was related to gemcitabine dose.…”
Section: Conditioning Regimens For Lymphoma G Damaj Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The GN-BVC regimen added gemcitabine and vinorelbine, two agents with demonstrated effi cacy in HL, and decreased the dose of BCNU with improvements in pulmonary toxicity and with encouraging FFP and OS (Arai et al 2010 ). The novel non-BCNU regimen using high-dose gemcitabine combined with busulfan and melphalan (GemBuMel) demonstrated an acceptable toxicity profi le and high activity as conditioning for adults with relapsed HL (Nieto et al 2011 ). These regimens have yet to be studied in the pediatric setting and studies in adults are limited by small patient numbers.…”
Section: Conditioning Regimens For Autologous Hctmentioning
confidence: 99%